L’impact d’une zone de libre-échange entre le Canada et les États-Unis : examen critique de l’étude de Wonnacott - Wilkinson, B. (L'Actualité économique, 1976)
AbstractThe Wonnacott study concludes that the most realistic and beneficial commercial policy Canada is likely to be able to pursue at the moment would be to negotiate a Canada-U.S. free trade arrangement. This paper consist primarily of assigning different weights to a variety of the considerations Wonnacott raises and analyzing the effects of these different weights on his conclusions regarding the appropriate free trade strategy for Canada. A number of issues are also raised which do not appear to have been examined in Wonnacott's analysis. The thrust of the paper is three-fold. First, there may not be as large a net economic benefits of Canada-United States free trade as the Wonnacott presentation suggests. Second, depending upon the weight one assigns to some of the political-economic factors, the advantages of the former policy may be reduced even more and accordingly we should not be stampeded into a bilateral Canada-United States agreement. And third, if any change in commercial policy is to have a maximum beneficial effect upon Canada, then regardless of what commercial policy is followed, more attention will have to be given to a number of broader issues such as Canadian practices and policies relating to its overall balance of payments (including capital inflows and their effects upon the Canadian dollar), and to protectionnist provincial policies encouraging the fragmentation of industry.